INTELLECTUAL CAPITAL, ENTREPRENEURIAL ORIENTATION, AND GREEN INNOVATION IN ITALIAN SMES - Giampaoli, Daniele; Sgrò, Francesca; Ciambotti, Massimo (Piccola Impresa / Small Business, 2025)
Purpose. This study aims to examine the relationships between IC, EO, and green innovation in Italian small and medium-sized enterprises (SMEs). Specifically, it investigates how different components of intellectual capital influence the dimensions of entrepreneurial orientation and how these, in turn, impact green innovation Design/methodology/approach . A structural model was developed and tested using data collected from a sample of 210 Italian SMEs. The model was analyzed using PLS-SEM technique. Findings. Results show that structural capital has a significant positive influence on all three dimensions of entrepreneurial orientation (innovativeness, proactiveness, and risk-taking). Human capital has a positive impact on risk-taking, while relational capital positively influences innovativeness. Among the EO dimensions, only innovativeness demonstrated a significant positive relationship with green innovation. Practical and Social implications. The study highlights the importance of SMEs investing in structural capital to foster entrepreneurial orientation. Moreover, it underscores the critical role of innovativeness in driving green innovation, suggesting that cultivating a culture of creativity and experimentation could be key to advancing environmental sustainability efforts. Originality of the study. This research contributes to the existing literature by providing empirical evidence on the interplay between IC, EO, and green innovation in the context of Italian SMEs. It offers a more nuanced understanding of how different components of intellectual capital influence specific dimensions of entrepreneurial orientation and how these translate into green innovation.